Effect of Tree Age Class and Storage on Germination Behaviour of some Important forest Tree Species of North-western Himalayas - , Atul; Sharma, Shivesh, Punam (Indian Forester, 2002)
Significantly higher germination in Albizia species was achieved within first eight days, when seeds of middle (32-48cm dbh) and mature (48-64cm dbh) trees i.e., of age class B or C, stored for six months were treated with acid and kept at 30Î¿C temperature conditions. In case of Acacia catechu, the seeds of mature tree (16-24cm dbh) i.e. age class C stored for a period of three or five months, treated with acid and germinated at 30Î¿C brought about significantly maximum increase in germination within only first six days. Irrespective of age class and incubation temperature, the seeds of Alnus nitida stored for a period of four months and treated with cold water showed significantly maximum germination within first fourteen days. A gradual but significant increase in germination tiJ1 fourteen days was noticed in seeds of Dalbergia sissoo which were stored for a period of six months, treated with cold water and incubated at 30Î¿C temperature condition. The various tree diameter age classes had no significant effect on germination in seeds of Alnus and Dalbergia sissoo species.